Intriguing Chinese characters - Miao Yaohua (Intriguing Chinese characters, 2017)
The book is particularly designed for readers in non-native Chinese environment. By years of accumulated experiences, the writer selects some frequently used characters that can be easily learned by target readers matching with abundant pictures. For readers' convenience, the book is arranged in alphabetical order.